Consensus organizing a community development workbook : a comprehensive guide to designing, implementing, and evaluating community change initiatives - Ohmer, Mary L.; DeMasi, Karen; Sage eBooks (London : SAGE, 2009)
The authors put the theory of consensus organising into practice through activities, case studies and the practical application of examples to real life situations.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Community development -- United States; Community organization -- United States; Consensus (Social sciences) -- United States; Electronic books